Pengaruh Partisipasi Kegiatan Boikot dan Loyalitas Pelanggan Terhadap Minat Beli Ulang Produk PT. Unilever Indonesia - Amirul Mukminin,; Achmad Syamsul Huda, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of customer loyalty on repurchase intention, as well as the role of boycott participation as a mediating variable. This research was conducted on Unilever customers in the Jabodetabek area by distributing questionnaires and using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method involving 215 respondents. The results showed that customer loyalty has a positive and significant effect on repurchase intention, while boycott participation was found to have no significant effect on consumers' decision to repurchase the products they have used. Validity and reliability tests state that the questionnaire instruments used in each variable have a good level of validity and reliability.